A multi-center, cross-sectional study on the burden of infectious keratitis in China. - Xiusheng Song; Lixin Xie; Xiaodong Tan; Zhichong Wang; Yanning Yang; Yuansheng Yuan; Yingping Deng; Shaoying Fu; Jianjiang Xu; Xuguang Sun; Xunlun Sheng; Qing Wang (PLoS ONE)
Objective To understand the prevalence and demographic characteristics of infectious keratitis and infectious corneal blindness. Methods A multi-center, population-based cross-sectional study was conducted from January 1 to August 31, 2010. A total of 191,242 individuals of all age groups from 10 geographically representative provinces were sampled using stratified, multi-stage, random and systematic sampling procedures. A majority, 168,673 (88.2%), of those sampled participated in the study. The examination protocol included a structured interview, visual acuity testing, an external eye examination, and an anterior segment examination using a slit lamp. The causes and sequelae of corneal disease were identified using uniform customized protocols. Blindness in one eye caused by infectious keratitis was defined as infectious corneal blindness. Results The prevalence of past and active infectious keratitis was 0.192% (95% confidence interval [CI], 0.171-0.213%), and the prevalence of viral, bacterial, and fungal keratitis was 0.11%, 0.075%, and 0.007%, respectively. There were 138 cases of infectious corneal blindness in at least one eye in the study population (prevalence of 0.082% [95%CI, 0.068%-0.095%]). Statistical analysis suggested that ocular trauma, alcoholic consumption, low socioeconomic levels, advanced age, and poor education were risk factors for infectious corneal blindness. Conclusions Infectious keratitis is the leading cause of corneal blindness in China. Eye care strategies should focus on the prevention and rehabilitation of infectious corneal blindness.